Identifikasi Literasi Sains sebagai Landasan Pengembangan Media Pembelajaran berbasis AI pada Program Studi PGSD - M. Misbachul Huda; Atika Maulidina Hs (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2025)
The challenges of 21st-century education demand a fundamental transformation in how prospective elementary school teachers understand and teach science. This study aims to identify the scientific literacy profile of elementary school teacher education (PGSD) students at STKIP Al Hikmah Surabaya as a baseline for developing AI-assisted learning media. The research employed a descriptive quantitative method with a survey design involving 68 students selected through purposive sampling. Data were collected using a standardized two-tier multiple-choice test adapted from PISA 2018 and TOSLS frameworks, covering content, process, and context dimensions. The results indicated that the majority of students (70.59%) reached the "High" category, while 26.47% were in the "Moderate" category. However, a significant disparity was found across dimensions: the content dimension showed a wide score range (55–85, mean 71), while the process dimension recorded the lowest individual score of 42 (mean 67). These findings suggest that while the overall average is sufficient, there is a sharp competency gap in conceptual mastery and scientific inquiry skills among individuals. Consequently, this study recommends the development of AI-Assisted Inquiry modules in the next phase of the research roadmap to provide personalized learning paths and scaffolding, specifically addressing the identified weaknesses in the process and content dimensions to ensure the quality of future science educators.